Fish hobbyists’ willingness to donate for wild fighting fish (Betta livida) conservation in Klang Valley - Abd Rahman, Muhammad Fairus (Multidisciplinary Digital Publishing Institute, 2021)
Betta livida is an endangered endemic species of wild fighting fish affected by habitat degradation and exploitation. Despite this concern, the literature on the conservation of wild betta is negligible. Conservation is a non-use value, whereas the species itself is a use-value because they are sought after in the ornamental fish trade business. Therefore, the contingent valuation method (CVM) was applied in this study to establish the monetary value for species conservation by determining hobbyists’ willingness to donate (WTD) for conservation. Fish hobbyists are the most prominent backbone of the industry and are the most acquainted with the targeted species. Hence, hobbyists’ knowledge, perceptions and attitude towards species conservation have also been explored and weighed against the WTD. Purposive sampling was employed with a total of 150 respondents in Klang Valley. The findings show that the WTD was influenced by double-bound CVM, age (AGE) and hobbyists who owned the species (OWNB). In contrast, knowledge, perceptions and attitudes were not significant. Using probit regression analysis, hobbyists’ WTD for species conservation was MYR 9.04 annually. The survey also revealed concern for species that are wild-caught by hobbyists. Hence, the results of this study offer preliminary insights into the WTD for wild betta and local freshwater fish conservation in Malaysia.